A framework for a civil engineering systems BOK. Issue 4 (1st October 2020) - Carmichael, David G.
ABSTRACT: The paper outlines what is believed to be a robust systems framework, suitable for the development of a Body of Knowledge in Civil Engineering Systems (BOK-CES). The proposed framework is structured in six parts, which are amplified and explained in the paper. The framework embodies, or is common to, all people's views on systems, provided terminology is revisited. The six parts are System; System Variables; System Models; Systems Modelling/Investigation; Systems Analysis; and Systems Synthesis. The framework has been tested on multiple pursuits. It applies whether the matter is probabilistic/deterministic, dynamic/static, discrete/continuous and other categorisations. It applies to both qualitative treatments and quantitative treatments. It is extendable beyond engineering. The paper is intended to promote discussion and debate on Civil Engineering Systems.